Health-washing strategies and practices: cases of AvenaCol and ProActiv - Tovar-Rivadeneyra, Andrea; Jiménez-Sánchez, Álvaro; López-Pastor, Ana-Teresa (Infonomy, 2024)
The growth in demand for health-promoting foods has prompted brands to develop marketing strategies that highlight the health benefits of their products. However, this trend has also led to the practice of health-washing, where benefits are exaggerated or distorted to attract consumers. This study analyses the cases of AvenaCol and ProActiv, two products that claim to lower cholesterol in various ways. Through a thematic discursive analysis of the content of their advertising messages and labels, the health and nutrition claims and the transparency of their communication are assessed. The results suggest that, although both products highlight perceived benefits, they tend to omit essential information on consumption and effectiveness, which can be misleading. This study concludes with a critical reflection on the ethical responsibility of brands in the health product sector and underlines the need for transparent communication to protect consumers and strengthen their trust in the food market.